2016
DOI: 10.1002/pbc.26227
|View full text |Cite
|
Sign up to set email alerts
|

Band 3 nullVIENNA, a novel homozygous SLC4A1 p.Ser477X variant causing severe hemolytic anemia, dyserythropoiesis and complete distal renal tubular acidosis

Abstract: We describe the second patient with anionic exchanger 1/band 3 null phenotype (band 3 null ), which was caused by a novel nonsense mutation c.1430C>A (p.Ser477X) in exon 12 of SLC4A1. We also update on the previous band 3 null patient, thereby elucidating the physiological implications of total loss of AE1/band 3. Besides transfusion-dependent severe hemolytic anemia and complete distal renal tubular acidosis, dyserythropoiesis was identified in the band 3 null patient, suggesting a role for band 3 in erythrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Moreover, mutations can arise in introns, resulting in abnormal mRNA processing or a premature termination codon [23-25]. SLC4A1 mutations also cause distal renal tubular acidosis, which has been observed along with HS in the same patient [26, 27]. …”
Section: Molecular Genetic Mechanisms Of Five Hs-related Genesmentioning
confidence: 99%
“…Moreover, mutations can arise in introns, resulting in abnormal mRNA processing or a premature termination codon [23-25]. SLC4A1 mutations also cause distal renal tubular acidosis, which has been observed along with HS in the same patient [26, 27]. …”
Section: Molecular Genetic Mechanisms Of Five Hs-related Genesmentioning
confidence: 99%
“…51 A promising strategy to elucidate the functions of these tightly connected molecule complexes could be a TREC-based analysis of red cells that lack some of the Rh complex constituents, as in Rh or Band3 deficiency, known to be associated with characteristic pathological signs. 50,52,53 Taken together, this nanoscale approach shows a homogenous distribution of 8.6 and 4.1 epitopes at the single molecule level. The realization using the homogeneity of RhD epitopes may aid in investigating the distribution and quantity of other red cell surface receptors.…”
Section: Lateral D Antigen Distribution Using High Resolution Trecmentioning
confidence: 69%
“…A truncated form of AE1 is expressed in the alpha-intercalated cells of the kidneys and is essential for acid secretion in the urine 1 . Loss of AE1 anion-transport activity in the kidney causes distal renal tubular acidosis (dRTA) and occurs when AE1 expression is severely reduced as in hereditary spherocytosis (HS) 10,11 or when kidney AE1 activity is severely reduced 1 or trafficking of kidney AE1 is impeded in the alpha-intercalated cell 1 .…”
Section: Sao Has a Distinctive Geographical Distribution Occurring Mmentioning
confidence: 99%
“…Homozygous SAO individuals, with no functioning AE1, and homozygous HS individuals, with no AE1, suffer from hemolytic anemia, dRTA and failure to thrive 3,10,11 . An in-depth study of homozygous SAO cells 13 , showed expression of SAO AE1 during erythropoiesis (in vitro) affected trafficking and cytokinesis resulting in numerous multinucleated erythroblasts and reduced proliferation and enucleation.…”
Section: Sao Has a Distinctive Geographical Distribution Occurring Mmentioning
confidence: 99%